2010
DOI: 10.1016/j.eswa.2010.04.044
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent phishing detection system for e-banking using fuzzy data mining

Abstract: Abstract-Detecting and identifying e-banking Phishing websites is really a complex and dynamic problem involving many factors and criteria. Because of the subjective considerations and the ambiguities involved in the detection, Fuzzy Data Mining Techniques can be an effective tool in assessing and identifying e-banking phishing websites since it offers a more natural way of dealing with quality factors rather than exact values. In this paper, we present novel approach to overcome the "fuzziness" in the e-banki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 166 publications
(91 citation statements)
references
References 25 publications
(19 reference statements)
0
91
0
Order By: Relevance
“…Hossain et al [22] aimed the fuzzy data mining e-banking phishing website exemplary which exhibitedconnotation and prominence of the e-banking phishing website criteria (URL & Domain Identity). It also revealed that even if some of the e-banking phishing website physiognomies or stratums are not very vibrant or not convinced, the website can still be phishy particularly when other phishing physiognomies or stratums are evident and flawless.…”
Section: Literature Analysismentioning
confidence: 99%
“…Hossain et al [22] aimed the fuzzy data mining e-banking phishing website exemplary which exhibitedconnotation and prominence of the e-banking phishing website criteria (URL & Domain Identity). It also revealed that even if some of the e-banking phishing website physiognomies or stratums are not very vibrant or not convinced, the website can still be phishy particularly when other phishing physiognomies or stratums are evident and flawless.…”
Section: Literature Analysismentioning
confidence: 99%
“…There was insignificant impact of the "Page Style" on "Social Human Factor" related features on the accuracy. Later in 2010 (13), the authors used the 27 features to build a model based on fuzzy-logic. Although, this is a promising solution it lacks to clarify how the features were extracted from the website, specifically features related to human-factors.…”
Section: Related Workmentioning
confidence: 99%
“…There was insignificant impact of the "Page Style" on "Social Human Factor criteria". Later on [18], the authors used the 27 features to build a model to predict websites type based on fuzzy data mining. Although, their method is a promising solution it did not clarify how the features were extracted from the website and specifically features related to human factors "Much Emphasis on Security and Response, Generic Salutation and Buying Time to Access Accounts".…”
Section: Related Workmentioning
confidence: 99%